Evolution and driving factors of “Production-living-ecological spaces” in mountainous counties: a case study of Tongdao County, Hunan Province - Cao, Hengyuan; Liu, Weidong; Liu, Minjie (Frontiers in Environmental Science, 2025)
Mountainous counties are under the twin pressure of urbanized development and resource extraction, and the conflict of “Production-Living-Ecological Spaces” is becoming more serious. Tongdao County, a typical mountainous county in the border area of Hunan, Guizhou, and Guangxi provinces, was selected as the research area based on the land use data, road data, and POI data from 2000 to 2020. This study developed spatial classification construction of PLES, incorporated landscape pattern index, and examined the temporal and spatial evolution of PLES. Utilizing GeoDetectors to pinpoint driving factors, and the following conclusions were drawn. First, it is clear that Tongdao County’s PLES is horizontally differentiated, with the ecological space predominating. The majority of the production space is situated in the area with gentle slope angles, and the living space is dispersed between the ecological and production spaces. Second, The PLES show obvious vertical differentiation, with the production space, living space, and weak ecological space all concentrated in the lower regions below the boundary line of 600 m in elevation and 8° in slope. The region below a height of 600 m is home to the majority of the strong ecological space. Third, PLES are significantly affected by water sources and roads, and the production and living spaces are typically located adjacent to these features. Finally, the development and evolution of PLES patterns are primarily influenced by natural geographical factors, with socioeconomic factors acting as the primary driving force. The interplay of these components results in a synergistic enhancing effect.